2007
DOI: 10.1038/sj.eye.6702933
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival injection of triamcinolone in the treatment of lid retraction of patients with thyroid eye disease: a case series

Abstract: Upper lid subconjunctival triamcinolone appears to be an effective treatment option in reducing lid retraction in patients with recent onset of thyroid eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 7 publications
0
28
0
1
Order By: Relevance
“…In addition, the subconjunctival injection into the upper lid may cause detachment of the levator aponeurosis and the Müller muscle from the tarsal plate. 27 Other potential adverse effects associated with triamcinolone, such as cataract and infection, were not observed in our study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, the subconjunctival injection into the upper lid may cause detachment of the levator aponeurosis and the Müller muscle from the tarsal plate. 27 Other potential adverse effects associated with triamcinolone, such as cataract and infection, were not observed in our study.…”
Section: Discussionmentioning
confidence: 58%
“…In a recent study, 3 of 4 patients in the congestive phase with upper lid retraction showed a favorable response to the triamcinolone injection; however, 1 patient in the fibrotic phase did not respond to the triamcinolone injections and required surgical correction. 27 The most common adverse effect of triamcinolone injection is an increase in intraocular pressure. 22,28 Topical steroids are more likely to cause an elevation in the intraocular pressure, and a periocular injection of a long-acting corticosteroid is the most dangerous route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Chee et al reported four cases treated with upper eyelid subconjunctival TA injections 53. Three of the four cases achieved resolution of retraction, eyelid position normalisation, seen in 6 to 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…In ophthalmology, subconjunctival TA has been used for anterior scleritis, 21 , 22 pterygium surgery, 23 superior limbic keratoconjunctivitis, 24 uveitis, corneal burns and ulcers, 8 intraocular surgery, 8 , 25 and thyroid eye disease 26 . Recently, its use has been reported to successfully reverse corneal graft rejection in posterior lamellar 27 and penetrating keratoplasties 28 …”
Section: Discussionmentioning
confidence: 99%